Imagery in the aftermath of viewing a traumatic film: using cognitive tasks to modulate the development of involuntary memory. - Deeprose, C; Zhang, S; Dejong, H; Dalgleish, T; Holmes, E (2012)
BACKGROUND AND OBJECTIVES: Involuntary autobiographical memories that spring unbidden into conscious awareness form part of everyday experience. In psychopathology, involuntary memories can be associated with significant distress. However, the cognitive mechanisms associated with the development of involuntary memories require further investigation and understanding. Since involuntary autobiographical memories are image-based, we tested predictions that visuospatial (but not other) established cognitive tasks could disrupt their consolidation when completed post-encoding. METHODS: In Experiment 1, participants watched a stressful film then immediately completed a visuospatial task (complex pattern tapping), a control-task (verbal task) or no-task. Involuntary memories of the film were recorded for 1-week. In Experiment 2, the cognitive tasks were administered 30-min post-film. RESULTS: Compared to both control and no-task conditions, completing a visuospatial task post-film reduced the frequency of later involuntary memories (Expts 1 and 2) but did not affect voluntary memory performance on a recognition task (Expt 2). LIMITATIONS: Voluntary memory was assessed using a verbal recognition task and a broader range of memory tasks could be used. The relative difficulty of the cognitive tasks used was not directly established. CONCLUSIONS: An established visuospatial task after encoding of a stressful experience selectively interferes with sensory-perceptual information processing and may therefore prevent the development of involuntary autobiographical memories.